Oxidative Generation of Boron-Centered Radicals in Carboranes - Mills, Harrison A. (J Am Chem Soc, 2020)
We report the first indirect observation and use of boron vertex-centered carboranyl radicals generated by the oxidation of modified carboranyl precursors. These radical intermediates are formed by the direct oxidation of a B─B bond between a boron cluster cage and an exopolyhedral boron-based substituent (e.g., −BF(3)K, −B(OH)(2)). The in situ generated radical species are shown to be competent substrates in reactions with oxygen-based radicals, dichalcogenides, and N-heterocycles, yielding the corresponding substituted carboranes containing B─O, B─S, B─Se, B─Te, and B─C bonds. Remarkably, this chemistry tolerates various electronic environments, providing access to facile substitution chemistry at both electron-rich and electron-poor B─H vertices in carboranes.